3D Flow Modeling of the First Trifurcation Made in Nepal - Malik, R K; Paudel, Paras (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
The foremost objective of the study was to find out the most efficient profile of trifurcation in given constraints of pressure, velocity and layout of the overall geometry. The study was done for the 3.2 MW Madi Khola Hydropower Project of Gandaki Hydropower Development Co. Pvt. Ltd. The 3 Dimensional Flow modeling of the trifurcation was based on the application of Computational Fluid Dynamics (CFD). The loss in the Trifurcation greatly depends upon its geometrical configuration. The research started with a general profi le and the flow pattern generated inside it was studied with the help of 3 Dimensional Flow modeling. The extent of vortex zone formation inside the trifurcation indicates the loss inside trifurcation. The profile of the trifurcation was hence changed to reduce the vortex formation as far as possible, till we get minimum possible loss. The profile under study should meet maximum flow efficiency under the physical constraints of fabrication. The flow efficient profile was then analyzed to capture the stress amplifi cation near junction. The reinforcing element in the form of steel T-section was added of different sectional values till the stress was within allowable limits under severe conditions. Key words: Symmetrical Trifuraction; Trifurcation; Computational fluid dynamics; Hydropower; Nepal DOI: 10.3126/hn.v5i0.2493 Hydro Nepal Vol. 5, July 2009 Page:56-61